Living in Two Worlds: An Institutional Ethnographic Study of the Family Reunification Process among Unaccompanied Minor and Young Refugee Girls in Norway - Ann-Torill Tørrisplass (Nordic Journal of Migration Research, 2024)
The increase in migration to Europe in 2015, which became known as the ‘refugee crisis’, led to a tightening of family reunification legislation in most European countries, including Norway. These legal measures, such as financial requirements, pose obstacles for unaccompanied minors and young refugees (UMs). They also have an impact on the work of the staff who support UMs with family reunification. In this article, I explore how UM girls experience the family reunification application process and how they and their municipal service providers navigate institutional systems during this process. Using an institutional ethnographic approach, this study explores the experiences of UM girls in three Norwegian municipalities. On the basis of data collected in these municipalities, I argue that policies and measures that prevent or restrict increased family immigration have a negative impact on UMs’ experiences of family reunification. Although not explicitly intended to harm children or deprive them of their rights, these restrictions on family reunification are at odds with Norway’s commitment to child welfare.